1974
DOI: 10.1016/0304-4211(74)90078-9
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal location of a gene that controls sterol esterification in Triticum Aestivum L.

Abstract: SUMMARYA previously described D genome locus (Pin) that controls sterol esterification in the wheat kernel has been assigned to the short arm of chromosome 7 D by comparison of the steryl ester phenotype of euploid kernels of Triticum aestivum variety Chinese Spring with those of the compensated nulli-tetrasomic lines and the 7 D S ditelosomic. Palmitate is the predominant ester in all but the 7 D nullisomic combinations, which have linoleate as the main ester. These lines also show a marked decrease in sterol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

1975
1975
1988
1988

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 9 publications
0
10
1
Order By: Relevance
“…The present results show that the differences in sterol ester pattern controlled by gene Pin are confined to the endosperm and that the previously observed difference in kernel free sterol between euploid Chinese Spring wheat and lines lacking chromosome 7D [15], also exist between the PL and the L phenotype varieties and is equally restricted to the same tissue (Table I). The higher sterol level cosegregates with the L phenotype pattern (Table II), which means that both features are controlled by the same mendelian factor or by two closely linked factors.…”
Section: Discussionmentioning
confidence: 52%
See 4 more Smart Citations
“…The present results show that the differences in sterol ester pattern controlled by gene Pin are confined to the endosperm and that the previously observed difference in kernel free sterol between euploid Chinese Spring wheat and lines lacking chromosome 7D [15], also exist between the PL and the L phenotype varieties and is equally restricted to the same tissue (Table I). The higher sterol level cosegregates with the L phenotype pattern (Table II), which means that both features are controlled by the same mendelian factor or by two closely linked factors.…”
Section: Discussionmentioning
confidence: 52%
“…Analysis of whole kernels of compensated nullitetrasomic and ditelosomic Unes of Triticum aestivum cv. Chinese Spring showed that gene Pin is located in the short arm of chromosome 7D [15]. Palmitate was found to be the dominant ester in all lines, except those lacking chromosome 7D, which had linoleate as the main ester.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations